อิทธิพลของเฟซบุ๊ค (Facebook) ต่อการมีส่วนร่วมทางการเมืองของข้าราชการตำรวจ สังกัดกองบังคับการตำรวจภูธรจังหวัดเชียงใหม่ - ธีรวัฒน์ อ้นจันทร์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The study "The Influence of Facebook Towards Political Participation of Police Officers in Chiang Mai Provincial Police Division" aimed to investigate the level of political participation through Facebook, explore the relationships between information received via Facebook and political participation, and find out the problems and obstacles affecting political participation through Facebook of the police officers in Chiang Mai Provincial Police Division. The samples in this qualitative study were 207 police officers working in administrative offices from police stations in Chiang Mai Provincial Police Division. The study revealed that 76.8% of the samples followed political news everyday. In addition, 45.4% of the samples used the Internet and Facebook only to gain access to the news but they did not use Facebook to participate in politics. Furthermore, the information gained from Facebook, via Post Items, Comments, Inbox, Notes, Events, Photos, and Videos, affected all 5 levels of political participation at a high level. These levels included level 1, following political news; level 2, voting in elections; level 3, persuading others to engage in political conversation; level 4, persuading others to vote in elections; and 5, using symbols to support political parties and candidates. Meanwhile, Facebook Chat affected level 2 at a low level, which was voting in elections; Groups affected level 3 at a low level, which was persuading others to engage in political conversation; and Document File affected level 4 at a low level, which was persuading others to vote in elections. In terms of problems and obstacles affecting political participation through Facebook of the police officers, it was found that the communication process, the civil servant status, and the current political situation resulted in the inability to gain reliable information via Facebook. In addition, because of these factors, police officers could not express their political views, which affected their political participation. For the recommendations, it can be suggested that a creative use of Facebook as a communication tool should be supported because it could lead to an appropriate political view expression among the police officers. Furthermore, guidelines of using online materials at police stations should be set. Also there should be training for police officers about online materials especially Facebook in order to develop positive attitudes towards the people, and use Facebook as a learning and opinion exchange tool. Finally, positive and creative political attitudes between police officers and the people should be developed.